The Welland inequality on hypergroups - Hajibayov, M. G. (Methods of Functional Analysis and Topology, 2019)
The Welland inequality for fractional integrals on hypergroups with quasi-metric and Haar measure is proved. This inequality gives pointwise estimates of fractional integrals by fractional maximal operators.